SEJARAH DALAM PERSPEKTIF AL-QURâAN - ibrahim, nasruddin (RIHLAH, 2013)
The history of human beings is an invaluable lesson, for it is rich with wisdoms. History contains significant events in the past is systematically organized and widely circulated to the societies as a repertoire of knowledge. History is an inherent element of human life, for history is an essential product of human civilization as well as a basic need of the human life per se. The Qurâan as a source of guidance integrates history into the moral narratives to provide moral lessons to human beings. It tells the stories of the societies in the past, their culture, civilization, and morality to serve as moral lessons that the current societies need to learn to maintain the harmony of their life.